Navigating diversity: Assessing gender inclusivity at the 2023 Association of Geographical Societies in Europe (EUGEO) Congress - Liliana Solé Figueras; Briana Bombana; Anna Ortiz Guitart (Documents d'Anàlisi Geogràfica)
Academic gender inequalities have been acknowledged as a long-standing issue. At conferences, a key arena for academic career development, these inequalities manifest themselves in various ways. This article aims to contribute to the debate on these issues by analysing, from a gender perspective, the EUGEO Geography Congress held in Barcelona in September 2023. The research comprises both quantitative and qualitative analysis. The main findings indicate some disparities in the number of male and female participants and in the evaluations and perceptions of men and women during the conference. While both genders generally provided positive evaluations of the conference, women placed greater emphasis on the supportive environment. Additionally, gender disparities were identified in debate participation and feelings, with women expressing less comfort and security during discussions. The research aims to contribute to reflections on gender representation at academic conferences and to provide ideas for possible strategies to foster greater inclusion at such conferences.